The political economy of the ambiguity of recognition: collective rights of indigenous people under Peruvian-style neoliberalism (1990-2000) - Salas, Fabio Manuel (Pontificia Universidad Católica del Perú, 2022)
The simultaneous appearance in 1989 of the term “Washington Consensus” and the adoption of ILO Convention 169 are not a historical curiosity, but rather a milestone in the ambiguity of the recognition of collective rights of indigenous people. Now, while the political economy of Peruvian development has been described as “heavily centralised and ethnically define exclusionary” (Orihuela, 2020, p. 146), can it be said that it only obeys the weight of history? What characterized the political economy of recognition during a markedly neoliberal period? The aim of this essay is to outline a proposal for analysis of the type of political economy that governed the recognition of indigenous people’s rights in Peru during the Fujimori decade (1990-2000). Although the historical determinants of the condition of exclusion of these people, the characteristics of the Peruvian neoliberal period and the underlying political economy have been studied, research focused on the relationship between these aspects at the end of the 20th century is scarce. The first section addresses the historical relationship between the people in question and the State; the second defines the concept of neoliberalism and its relationship with collective rights; the third section develops the analysis proposal. Finally, it is argued that the “recognition” of the right to land and territory under the Fujimori regime implied a lack of knowledge, constraint and violation of this and other collective rights of indigenous people.

La simultánea aparición en 1989 del término “Consenso de Washington” y la adopción del Convenio 169 de la OIT no son una curiosidad histórica, sino, más bien, un hito en la ambigüedad del reconocimiento de los derechos colectivos de los pueblos indígenas. Ahora bien, en tanto la economía política del desarrollo peruano ha sido descrita como “fuertemente centralizada y étnicamente excluyente”* (Orihuela, 2020, p. 146), ¿puede afirmarse que solo obedece al peso de la historia? ¿Qué caracterizó a la economía política del reconocimiento durante un periodo marcadamente neoliberal? El objetivo del ensayo es esbozar una propuesta de análisis del tipo de economía política que rigió el reconocimiento de los derechos de los pueblos indígenas en el Perú durante la década fujimorista (1990-2000). Si bien se han estudiado los determinantes históricos de la condición de exclusión de estos pueblos, las características del periodo neoliberal peruano y la economía política subyacente, las investigaciones enfocadas en la relación entre estos aspectos a finales de siglo XX son escasas. La primera sección aborda la relación histórica entre los pueblos en cuestión y el Estado; la segunda delimita el concepto de neoliberalismo y su relación con los derechos colectivos; la tercera sección desarrolla la propuesta de análisis. Finalmente, se arguye que el “reconocimiento” del derecho a la tierra y territorio bajo el régimen fujimorista, en realidad, implicó un desconocimiento, constreñimiento y vulneración de este y otros derechos colectivos de los pueblos indígenas.
La economía política de la ambigüedad del reconocimiento: derechos colectivos de los pueblos indígenas bajo el neoliberalismo à la peruana (1990-2000)
The political economy of the ambiguity of recognition: collective rights of indigenous people under Peruvian-style neoliberalism (1990-2000)
Keywords: Political economy; Collective rights; Indigenous people; Neoliberalism in Peru; Economía política; Derechos colectivos; Pueblos indígenas; Eoliberalismo en el Perú; https://purl.org/pe-repo/ocde/ford#5.04.01